2020
DOI: 10.1007/s11548-020-02276-y
|View full text |Cite
|
Sign up to set email alerts
|

Toward interprofessional team training for surgeons and anesthesiologists using virtual reality

Abstract: Purpose In this work, a virtual environment for interprofessional team training in laparoscopic surgery is proposed. Our objective is to provide a tool to train and improve intraoperative communication between anesthesiologists and surgeons during laparoscopic procedures. Methods An anesthesia simulation software and laparoscopic simulation software are combined within a multi-user virtual reality (VR) environment. Furthermore, two medical training scenarios for communication training between anesthesiologis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 29 publications
0
17
0
8
Order By: Relevance
“…Some argued that high up-front expenses created barriers to implementation and maintenance, including purchasing simulators and headsets as well as software licenses, technology maintenance, staff training, and programming requirements [ 26 , 76 , 91 - 95 ]. Integrating VR or AR with manikins was reported to significantly increase costs further [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some argued that high up-front expenses created barriers to implementation and maintenance, including purchasing simulators and headsets as well as software licenses, technology maintenance, staff training, and programming requirements [ 26 , 76 , 91 - 95 ]. Integrating VR or AR with manikins was reported to significantly increase costs further [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Developmental and logistical considerations further create barriers because implementing and maintaining VR and AR programs requires imagination, resources, and planning [ 94 ]. From conception, the design and development of training resources can be a lengthy and complicated process, requiring specific programming and animation expertise [ 17 , 26 , 34 , 91 ]. Design needs to be multidisciplinary (to convey accurate content), attractive, and user centered [ 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this context and maybe more in an emergency scenario, a team of well-trained people is the key factor for a successful robotic program [ 110 ] and should represent the standard also in emergency MIS. Some strategies to ameliorate team work were described, and the emerging solutions to improve technical skills and communication rely on simulation [ 111 114 ].…”
Section: Resultsmentioning
confidence: 99%
“…A multiplayer design within the XR environment is thought to be able to offer a chance to rotate through different team roles, supporting an active and immersive learning experience with the potential to equip the learners with the crucial teamwork skills required for medical care [ 25 ]. Chheang et al [ 27 ] established anesthesia simulation software and laparoscopic simulation software that were combined within a multiuser VR environment; the interaction of multiplayers could be fulfilled in the virtual world. It was revealed that the multiuser-based software could improve problem-based communication during surgery.…”
Section: Discussionmentioning
confidence: 99%